Feasibility Of Prescription Pesticide Use In The United States - Coble, Harold D.; Bonanno, A. Richard; Mcgaughey, Bernalyn; Purvis, George A.; Zalom, Frank G. (Council for Agricultural Science and Technology (CAST), 1998)
Discussion of the feasibility of applying the medical model of prescriptions to high-risk pesticides that are being reassessed following passage by Congress of the Food Quality Protection Act (FQPA) in 1996.